Novas vozes para novos tempos: o surgimento do intelectual católico moderno - Nascimento, Rhuan Reis do (Sacrilegens, 2022)
The Catholic Church faced a serious crisis of authority during the 19th century. The advent of modernity reduced the cultural influence of the Church as it pushed religiosity into the private sphere and made priests faze difficulties in interfering in political and social issues. In this context, the catholic lay intellectual, endowed with academic authority and active in the press, stood out in the defense of catholic values. The first group of catholic intelectuals to gain notoriety were french thinkers who were active in the early 20th century. The catholic lay intellectual, about whom our article deals, played an important role in shaping the relationshp between catholicism and modern society.